Preparation method and application of lithium manganese iron phosphate secondary microspheres with porous structures
Porous lithium iron manganese phosphate secondary microspheres were prepared by co-precipitation and spray drying, which solved the problems of low electronic conductivity and slow lithium ion diffusion rate of LiMn1-xFexPO4 materials, significantly improving the electrochemical activity of the material and lithium-ion batteries. charge and discharge performance.
Patent Information
- Application Number
- CN202411522203.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-24
AI Technical Summary
The low electronic conductivity of LiMn1-xFexPO4 material and slow diffusion rate of lithium ions lead to low electrochemical activity, and the Jahn-Teller effect of Mn3+ leads to lattice distortion and manganese dissolution at the electrode/electrolyte interface, resulting in capacity attenuation.
The co -sedimentation legal preparation of manganese phosphate iron front -drive body is used, and a secondary microsphere of lithium manganese iron phosphate iron phosphate iron phosphate iron phosphate iron phosphate is used to form a carbon coverage structure to improve the electrical and lithium ion diffusion capacity of the material.
Through the secondary microspheres of lithium manganese iron phosphate prepared by the co -sedimentation method and spray drying legal system, the electronic conductivity and lithium ion diffusion rate of the material are significantly improved, and the electrochemical activity and the charging and discharge performance of the lithium ion battery are enhanced.
Smart Images

Figure CN119361689A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and specifically relates to a method for preparing a flaky manganese iron phosphate precursor and porous manganese iron phosphate lithium secondary microspheres by a coprecipitation method. Background Art
[0002] With the growing energy crisis and emerging environmental problems, lithium-ion batteries (LIBs) have broad development prospects due to their high operating voltage and energy density, low toxicity and environmental friendliness of electrode materials. Among various positive electrode materials, lithium iron phosphate (LiFePO4, LFP) has a stable discharge platform (3.4V), high theoretical discharge capacity (170mAh·g -1 ), thermal stability, long life and low cost, and occupies more than one-third of the lithium-ion battery (LIBs) market. However, LFP has the disadvantages of low discharge voltage and low energy density, which seriously hinders its further development. Another lithium-ion battery positive electrode material, lithium manganese phosphate (LiMnPO4, LMP), is mainly composed of element Mn and has a higher discharge platform (4.1V). However, LMP occurs during the charge and discharge process (Mn 2+ / Mn 3+ ) redox reaction, high spin Mn 3+ It will cause the Jahn-Teller effect, which will seriously affect the improvement of its electrochemical performance. x Fe 1-x PO4, LMFP) combines the advantages of LFP and LMP, has higher energy density, and will be an alternative strategy for achieving high-performance cathode materials. However, due to its discontinuous b-axis (one-dimensional lithium ion diffusion channel), its lithium ion diffusion rate is slow; at the same time, due to the uneven distribution of iron and manganese atoms, the reversible capacity is reduced, which hinders its practical application.
[0003] In the process of in-depth research on LMFP materials, researchers mainly focus on three key technical directions, aiming to significantly improve the electronic and ionic conductivity of LMFP solid solution through various strategies, thereby optimizing its application in lithium-ion batteries. These three key technical directions include: (1) Nano-scaling: By nano-scaling LMFP materials, not only can the surface area of the material in contact with the electrolyte be greatly increased, thereby accelerating the transmission speed of ions, but it can also help shorten the diffusion path of lithium ions inside the electrode material and improve the battery's charge and discharge performance. (2) Conductive agent coating: By coating a layer of conductive material, such as carbon, conductive polymer, etc. on the surface of the LMFP material. This coating layer not only improves the electronic conductivity of the material, but also prevents the electrode material from directly contacting the electrolyte and reducing the occurrence of side reactions. (3) Element doping: By introducing other elements, such as magnesium (Mg), cobalt (Co), nickel (Ni), etc., into the LMFP lattice, its internal electron distribution and ion diffusion channel size can be effectively adjusted, thereby improving the electrochemical performance of the material.
[0004] At present, the method for large-scale production of LMFP is mostly high-temperature solid phase method, but this method is difficult to make the transition metal evenly distributed in the main structure of the material, resulting in Mn 3+ The Jahn-Teller effect is serious, and it is difficult to control the particle size and morphology, which affects the diffusion of lithium ions. Although the hydrothermal method / solvothermal method can obtain materials with uniform particle size and special morphology, the reaction time is long and high-pressure resistant equipment is required. At the same time, the subsequent treatment of organic solvents will increase costs.
[0005] In summary, it is of great significance to develop a lithium manganese iron phosphate positive electrode material with simple process, low cost and excellent performance. Summary of the invention
[0006] The purpose of the present invention is to solve the problem of LiMn 1-x Fe x The inherent low electronic conductivity of PO4 and Li + The slow diffusion rate leads to low electrochemical activity of the material, and Mn 3+ The Jahn-Teller effect causes lattice distortion, which causes manganese to dissolve at the electrode / electrolyte interface and leads to capacity decay and other problems. A method for preparing lithium manganese iron phosphate secondary microspheres with a porous structure and applications are provided.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing lithium manganese iron phosphate secondary microspheres with a porous structure, the method comprising:
[0009] (1) Preparing a ferromanganese phosphate precursor: using a coprecipitation method, an iron source, a manganese source and a surfactant are mixed in deionized water to form a uniform solution; then a phosphorus source is added and the pH of the solution is controlled by slowly dropping an ammonia solution to perform a coprecipitation reaction, and after the reaction is complete, aging is performed, and solid-liquid separation is performed to obtain a ferromanganese phosphate precursor;
[0010] (2) Preparation of lithium iron manganese phosphate: mixing a manganese iron phosphate precursor with a lithium source and a carbon source in deionized water, and ball milling to prepare lithium iron manganese phosphate;
[0011] (3) Preparation of carbon-coated lithium manganese iron phosphate: The obtained ball-milled slurry is spray-dried and calcined under an inert atmosphere to obtain carbon-coated lithium manganese iron phosphate.
[0012] (4) Assemble button-type half-cells. Place the prepared positive electrode sheet in the center of the 2025 positive electrode shell in turn; use a pipette to add electrolyte, and place the diaphragm on top of the positive electrode sheet; use a pipette to add electrolyte, take the lithium sheet and place it in the center of the diaphragm, and then put in the nickel foam; use a pipette to add electrolyte, and then take the negative electrode shell to cover it; then place the button cell on a sealing machine and press it to complete the assembly and preparation of the button cell.
[0013] Furthermore, in step (1), the iron source is any one of ferrous sulfate, ferrous chloride, ferrous nitrate or ferrous oxalate, or a combination of at least two thereof; the manganese source is any one of manganese sulfate, manganese chloride or manganese oxalate, or a combination of at least two thereof; the phosphorus source is at least one of phosphoric acid, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate; the surfactant is any one of ethylenediaminetetraacetic acid, polyvinylpyrrolidone or ethylenediamine, or a combination of at least two thereof, and ethylenediaminetetraacetic acid is further preferred.
[0014] Furthermore, in step (1), the iron salt, manganese salt, phosphorus source and surfactant are prepared in a molar ratio of 1:1:2 to 2.05:0.08, wherein the solubility of the uniform solution formed by the iron salt, manganese salt and surfactant is 0.136-1.500 mol / L, and a coprecipitation reaction is carried out at 50-80°C; the solution pH is controlled to be 5-7, the reaction time is 8-24h, the aging time is 6-24h, and the manganese ferrophosphate precursor is obtained by washing, filtering and vacuum drying.
[0015] Furthermore, in step (2), the carbon source is any one of glucose, sucrose or starch, or a combination of at least two of them; the lithium source is any one of lithium hydroxide, lithium carbonate, lithium acetate, lithium acetate or lithium chloride, or a combination of at least two of them.
[0016] Furthermore, in step (2), the ferromanganese phosphate and the lithium source are prepared in a molar ratio of 1:1 to 1.05, the carbon source is added at 10% to 30% of the mass of the ferromanganese phosphate, the solubility of lithium in the evenly mixed solution is 0.348-1.739 mol / L, the ball milling speed is 150-350 r / min, and the ball milling time is 2-8 h.
[0017] Furthermore, in step (3), when the secondary microspheres are prepared by spray drying, the air inlet temperature is 200-250°C, the air outlet temperature is 100-120°C, and the nozzle pressure is 0.1-0.3Mpa.
[0018] Furthermore, in step (3), the high temperature calcination temperature is 500-800°C, the time is 2-10h, the heating rate is 3-10°C / min, and the inert protective gas is a combination of one or more gases selected from nitrogen, argon, helium and hydrogen.
[0019] An application of lithium iron manganese phosphate secondary microspheres prepared by the above preparation method in a lithium ion battery, wherein the lithium ion battery comprises a positive electrode, a negative electrode and a separator, wherein the positive electrode material used comprises lithium iron manganese phosphate secondary microspheres.
[0020] In step (4), the positive electrode sheet is prepared using N-methylpyrrolidone (NMP) as solvent, and the slurry ratio is: the prepared carbon-coated lithium manganese iron phosphate (LiMn 0.5 Fe 0.5 PO4 / C): conductive agent (Super-P): polyvinylidene fluoride (PVDF) = 8:1:1, after coating with aluminum foil, drying at 80℃ for 10h. The electrolyte is 1M lithium hexafluorophosphate (LiPF6) dissolved in ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) (1:1:1, V / V / V). The negative electrode is a commercial lithium sheet. The diaphragm is a commercial diaphragm.
[0021] The beneficial effects of the present invention compared to the prior art are:
[0022] (1) The present invention adopts a coprecipitation method to prepare a manganese ferrophosphate precursor, the chemical formula of which is Mn 0.5 Fe 0.5 PO4, in the same ratio of manganese and iron, makes it precipitate evenly, which is conducive to the uniform mixing of manganese and iron atoms and improves the Mn 3+ The Jahn-Teller effect problem.
[0023] (2) In the presence of surfactant, the formation of a sheet-like ferromanganese phosphate precursor is induced, shortening the Li + diffusion paths, thereby improving conductivity.
[0024] (3) Spray drying converts the flaky primary lithium iron manganese phosphate into porous secondary lithium iron manganese phosphate microspheres. The porous structure is conducive to electrolyte infiltration, shortens the ion transmission distance, and accelerates the electrochemical reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of the porous lithium manganese iron phosphate secondary microspheres of Example 1 at 3000 times magnification;
[0026] Figure 2 This is a SEM image of the flake-like primary nanoparticle manganese iron phosphate of Example 1 at a magnification of 50,000 times. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The present invention prepares the desired product by dissolving different raw materials through a coprecipitation method and adjusting the pH to achieve the coprecipitation conditions, thereby obtaining a sheet-like nano-manganese iron phosphate precursor, and then spray drying is used to prepare porous lithium iron manganese phosphate secondary microspheres with special morphology and high rate performance. The coprecipitation method allows iron and manganese to be evenly mixed at the atomic level, while controlling the morphology to prepare a nano-sheet manganese iron phosphate precursor, shortening the diffusion distance of lithium ions. Spray drying prepares secondary microspheres with a porous structure, which is conducive to the penetration of the electrolyte, thereby preparing LiMn with high capacity and high rate performance. 0.5 Fe 0.5 PO4 / C positive electrode material.
[0029] Example 1
[0030] (1) 0.075 mol MnSO4, 0.075 mol FeSO4 and 0.006 mol ethylenediaminetetraacetic acid were added to 250 ml deionized water and stirred for 2 h to form a uniform solution. A small amount of ascorbic acid (0.001 mol) was added during the stirring process to prevent Fe 2+ Oxidized to Fe 3+ . Add 150 ml of deionized water containing 0.15 mol H3PO4 to the homogeneous solution and stir for 0.5 h, and slowly add ammonia water to adjust the solution pH to 6, control the reaction temperature to 70 ° C, the speed to 400 rpm, the reaction time to 12 h, and age for 12 h. Wash thoroughly with deionized water and collect the precipitate by suction, and dry it at 100 ° C overnight under vacuum conditions.
[0031] (2) 10 g of the ferromanganese phosphate precursor prepared in (1) and 1.8 g of glucose were mixed evenly in 100 ml of deionized water. In addition, 1.59 g of LiOH was added as a lithium source to prepare LiMn 0.5 Fe 0.5 PO4, and 5 mol% LiOH was added to prevent the loss of lithium during calcination. LiMn was obtained by ball milling at 200 r / min for 4 h. 0.5 Fe 0.5 PO4 stabilized slurry.
[0032] (3) The obtained slurry was spray dried to prepare secondary microspheres, and the air inlet temperature was set to 220°C, the air outlet temperature was set to 107°C, and the nozzle pressure was set to 0.2 MPa. The collected yellow powder was then calcined at high temperature in a tubular furnace in a nitrogen atmosphere to prepare LiMn 0.5 Fe 0.5 PO4 / C, naturally cooled to room temperature, and collected the material. The heating rate was set to 5℃ / min, 350℃ for 2h, and 650℃ for 6h.
[0033] Example 2
[0034] The difference from Example 1 is that the preparation method of this Example (1) is as follows: 0.075 mol MnSO4, 0.075 mol FeSO4 and 0.006 mol surfactant polyvinyl pyrrolidone are added to 250 ml deionized water respectively and stirred for 2 hours to form a uniform solution.
[0035] Example 3
[0036] The difference from Example 1 is that the preparation method of this Example (1) is as follows: 0.075 mol MnSO4, 0.075 mol FeSO4 and 0.006 mol surfactant ethylenediamine are added to 250 ml deionized water respectively and stirred for 2 hours to form a uniform solution.
[0037] Example 4
[0038] (1) 0.075 mol MnSO4, 0.075 mol FeSO4 and 0.006 mol ethylenediaminetetraacetic acid were added to 250 ml deionized water and stirred for 2 h to form a uniform solution. A small amount of ascorbic acid (0.001 mol) was added during the stirring process to prevent Fe 2+ Oxidized to Fe 3+. Add 150 ml of deionized water containing 0.15 mol H3PO4 to the homogeneous solution and stir for 0.5 h, and slowly add ammonia water to adjust the solution pH to 6, control the reaction temperature to 70 ° C, the speed to 400 rpm, the reaction time to 12 h, and age for 12 h. Wash thoroughly with deionized water and collect the precipitate by suction, and dry it at 100 ° C overnight under vacuum conditions.
[0039] (2) 10 g of the ferromanganese phosphate precursor prepared in (1) and 1.2 g of glucose were mixed evenly in 100 ml of deionized water. In addition, 1.59 g of LiOH was added as a lithium source to prepare LiMn 0.5 Fe 0.5 PO4, and 5 mol% LiOH was added to prevent the loss of lithium during calcination. LiMn was obtained by ball milling at 200 r / min for 4 h. 0.5 Fe 0.5 PO4 stabilized slurry.
[0040] (3) The obtained slurry was spray dried to prepare secondary microspheres, and the air inlet temperature was set to 220°C, the air outlet temperature was set to 107°C, and the nozzle pressure was set to 0.2 MPa. The collected yellow powder was then calcined at high temperature in a tubular furnace in a nitrogen atmosphere to prepare LiMn 0.5 Fe 0.5 PO4 / C, naturally cooled to room temperature, and collected the material. The heating rate was set to 5℃ / min, 350℃ for 2h, and 600℃ for 10h.
[0041] Example 5
[0042] (1) 0.075 mol MnSO4, 0.075 mol FeSO4 and 0.006 mol ethylenediaminetetraacetic acid were added to 250 ml deionized water and stirred for 2 h to form a uniform solution. A small amount of ascorbic acid (0.001 mol) was added during the stirring process to prevent Fe 2+ Oxidized to Fe 3+ . Add 150 ml of deionized water containing 0.15 mol H3PO4 to the homogeneous solution and stir for 0.5 h, and slowly add ammonia water to adjust the solution pH to 6, control the reaction temperature to 70 ° C, the speed to 400 rpm, the reaction time to 12 h, and the aging to 12 h. Wash thoroughly with deionized water and collect the precipitate by suction, and dry it at 100 ° C overnight under vacuum conditions.
[0043] (2) 10 g of the ferromanganese phosphate precursor prepared in (1) and 2.5 g of glucose were mixed evenly in 100 ml of deionized water. In addition, 1.59 g of LiOH was added as a lithium source to prepare LiMn 0.5 Fe 0.5PO4, and 5 mol% LiOH was added to prevent the loss of lithium during calcination, and LiMn was obtained by ball milling at 200 r / min for 4 h. 0.5 Fe 0.5 PO4 stabilized slurry.
[0044] (3) The obtained slurry was spray dried to prepare secondary microspheres, and the air inlet temperature was set to 220°C, the air outlet temperature was set to 107°C, and the nozzle pressure was set to 0.2 MPa. The collected yellow powder was then calcined at high temperature in a tubular furnace in a nitrogen atmosphere to prepare LiMn 0.5 Fe 0.5 PO4 / C, naturally cooled to room temperature, and collected the material. The heating rate was set to 5℃ / min, 350℃ for 2h, and 700℃ for 4h.
[0045] Comparative Example 1
[0046] (1) 0.075 mol MnSO4 and 0.075 mol FeSO4 were added to 250 ml deionized water and stirred for 2 h to form a uniform solution. A small amount of ascorbic acid (0.001 mol) was added during the stirring process to prevent Fe 2+ Oxidized to Fe 3+ . Add 150 ml of a solution containing 0.15 mol H3PO4 to the homogeneous solution and stir for 0.5 h, and slowly add ammonia water to adjust the solution pH to 6, control the reaction temperature to 70 ° C, the speed to 400 rpm, the reaction time to 12 h, and age for 12 h. Wash thoroughly with deionized water and collect the precipitate by suction, and dry it at 100 ° C overnight under vacuum conditions.
[0047] (2) 10 g of ferromanganese phosphate and 1.8 g of glucose were mixed evenly in 100 ml of deionized water. In addition, 1.59 g of LiOH was added as a Li source to prepare LiMn 0.5 Fe 0.5 PO4, and 5 mol% LiOH was added, and the mixture was ball-milled at 200 r / min for 4 h to obtain LiMn 0.5 Fe 0.5 PO4 stabilized slurry.
[0048] (3) The obtained slurry was spray dried to prepare secondary microspheres, and the air inlet temperature was set to 220°C, the air outlet temperature was set to 107°C, and the nozzle pressure was set to 0.2 MPa. The collected yellow powder was then calcined at high temperature in a tubular furnace in a nitrogen atmosphere to prepare LiMn 0.5 Fe 0.5 PO4 / C, naturally cooled to room temperature, and collected the material. The heating rate was set to 5℃ / min, 350℃ for 2h, and 650℃ for 6h.
[0049] To better illustrate the effect of the embodiment of the present invention, assemble a button half-battery, place the prepared positive electrode sheet in the center of the 2025 positive electrode shell in turn; use a pipette to add electrolyte, and place the diaphragm above the positive electrode sheet; use a pipette to add electrolyte, take a lithium sheet and place it in the center of the diaphragm, and then put in nickel foam; use a pipette to add electrolyte, and then take the negative electrode shell to cover; then place the button battery on a sealing machine to press and complete the assembly and preparation of the button battery. The preparation of the positive electrode sheet uses N-methylpyrrolidone (NMP) as the solvent, and the ratio of the slurry is: the prepared carbon-coated lithium manganese iron phosphate (LiMn 0.5 Fe 0.5 PO4 / C): conductive agent (Super-P): polyvinylidene fluoride (PVDF) = 8:1:1, after coating with aluminum foil, drying at 80°C for 10h. The electrolyte is 1M lithium hexafluorophosphate (LiPF6) dissolved in ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) (1:1:1, V / V / V). The negative electrode is a commercial lithium sheet. The diaphragm is a commercial diaphragm. The following provides comparative test results of the embodiments and comparative examples and the assembled lithium-ion batteries.
[0050] Table 1 Electrochemical properties of lithium manganese iron phosphate cathode materials
[0051]
Claims
1. A method for preparing lithium manganese iron phosphate secondary microspheres with a porous structure, characterized in that: The method is: (1) Preparing a ferromanganese phosphate precursor: using a coprecipitation method, an iron source, a manganese source and a surfactant are mixed in deionized water to form a uniform solution; then a phosphorus source is added and the pH of the solution is controlled by slowly dropping an ammonia solution to perform a coprecipitation reaction, and after the reaction is complete, aging is performed, and solid-liquid separation is performed to obtain a ferromanganese phosphate precursor; (2) Preparation of lithium iron manganese phosphate: mixing a manganese iron phosphate precursor with a lithium source and a carbon source in deionized water, and ball milling to prepare lithium iron manganese phosphate; (3) Preparation of carbon-coated lithium manganese iron phosphate: The obtained ball-milled slurry is spray-dried and calcined under an inert atmosphere to obtain carbon-coated lithium manganese iron phosphate.
2. The preparation method according to claim 1, characterized in that: In step (1), the iron source is any one of ferrous sulfate, ferrous chloride, ferrous nitrate or ferrous oxalate, or a combination of at least two thereof; the manganese source is any one of manganese sulfate, manganese chloride or manganese oxalate, or a combination of at least two thereof; the phosphorus source is at least one of phosphoric acid, diammonium hydrogen phosphate and ammonium dihydrogen phosphate; and the surfactant is any one of ethylenediaminetetraacetic acid, polyvinylpyrrolidone or ethylenediamine, or a combination of at least two thereof.
3. The preparation method according to claim 1, characterized in that: In step (1), the iron salt, manganese salt, phosphorus source and surfactant are prepared in a molar ratio of 1:1:2 to 2.05:0.08, wherein the solubility of the uniform solution formed by the iron salt, manganese salt and surfactant is 0.136-1.500 mol / L, and a coprecipitation reaction is carried out at 50-80°C; the solution pH is controlled to be 5-7, the reaction time is 8-24h, the aging time is 6-24h, and the manganese ferrophosphate precursor is obtained through washing, suction filtration and vacuum drying.
4. The preparation method according to claim 1, characterized in that: In step (2), the carbon source is any one of glucose, sucrose or starch, or a combination of at least two of them; the lithium source is any one of lithium hydroxide, lithium carbonate, lithium acetate, lithium acetate or lithium chloride, or a combination of at least two of them.
5. The preparation method according to claim 1, characterized in that: In step (2), the ferromanganese phosphate and the lithium source are prepared in a molar ratio of 1:1 to 1.05, the carbon source is added at 10% to 30% of the mass of the ferromanganese phosphate, the solubility of lithium element in the uniformly mixed solution is 0.348-1.739 mol / L, the ball milling speed is 150-350 r / min, and the ball milling time is 2-8 h.
6. The preparation method according to claim 1, characterized in that: In step (3), when the secondary microspheres are prepared by spray drying, the air inlet temperature is 200-250°C, the air outlet temperature is 100-120°C, and the nozzle pressure is 0.1-0.3Mpa.
7. The preparation method according to claim 1, characterized in that: In step (3), the high temperature calcination temperature is 500-800°C, the time is 2-10h, the heating rate is 3-10°C / min, and the inert protective gas is a combination of one or more gases selected from nitrogen, argon, helium and hydrogen.
8. Use of lithium iron manganese phosphate secondary microspheres prepared by the preparation method according to any one of claims 1 to 7 in lithium ion batteries, characterized in that: The lithium-ion battery comprises a positive electrode, a negative electrode and a separator, wherein the positive electrode material comprises lithium manganese iron phosphate secondary microspheres.
Citation Information
Cited By
Lithium manganese iron phosphate positive electrode active material and preparation method therefor, positive electrode sheet, lithium secondary battery, and electric device
WO2026157136A1